Digitalisasi Bank Sampah “Sugema” Sebagai Pusat Edukasi Pengelolaan Sampah di Kelurahan Kotabaru Kecamatan Cibeureum Kota Tasikmalaya - Setiadi, Pidi Muhammad; Respati, Resa; Alia, Dwi; Lidinillah, Dindin Abdul Muiz; Gandana, Gilar; Nugraha, Dadan (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2024)
In 2020, Tasikmalaya City as an area that contributes 106 thousand tons of waste per year, if calculated per person, it will produce 0.44 kg of waste per day. In response to this, residents in the Perum Kotabaru Kencana RW 018 Kelurahan Kotabaru, Cibeureum District, Tasikmalaya City established the "SUGEMA" or "SUpaya GEde MAngfaatna" Waste Bank. The purpose of the "Sugema" Waste Bank is as a center for waste management and utilization, a center for waste management education, as well as a production center and distribution center for processed waste products. However, its management is still manual and not digital-based, so it requires innovation such as digital-based educational applications or media. Based on these problems, the solution is to create an application for waste management and create digital-based educational media to educate the public in waste management. The method used is the science and technology diffusion method which is defined as the activity of disseminating or applying science and technology to the wider community or partner groups. The output is waste management educational applications and media.